2021
DOI: 10.1002/adfm.202010394
|View full text |Cite
|
Sign up to set email alerts
|

Induced Chiral Chromonics Confined in Micrometric Droplets

Abstract: Chirality emergence in biological systems is common but the chiral expression from the molecular to macroscopic level in water‐based systems is poorly understood. Among water‐based systems, chromonic liquid crystals have recently received a lot of attention due to the spontaneous chirality they show when confined in curved geometries. Confinement of chiral‐induced chromonics is not trivial since they are three component systems whose time stability is a delicate thermodynamic balance. In this work, a well‐defi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

4
10
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6
1

Relationship

2
5

Authors

Journals

citations
Cited by 8 publications
(14 citation statements)
references
References 24 publications
4
10
0
Order By: Relevance
“…If refrigerated at 4 • C, the texture is preserved for two weeks. From previous observations [13] we have found that oxazine 725 improves the quality of the Frank-Price texture (Figure 4c and 4d). Figure 5c and Figure 5d show, in the case of DSCG containing L-alanine, that the number of microspheres with a well-defined texture increases when the material is doped with oxazine.…”
Section: Pom Measurementssupporting
confidence: 60%
See 3 more Smart Citations
“…If refrigerated at 4 • C, the texture is preserved for two weeks. From previous observations [13] we have found that oxazine 725 improves the quality of the Frank-Price texture (Figure 4c and 4d). Figure 5c and Figure 5d show, in the case of DSCG containing L-alanine, that the number of microspheres with a well-defined texture increases when the material is doped with oxazine.…”
Section: Pom Measurementssupporting
confidence: 60%
“…Chiral textures in microspheres are also easily measurable with a polarized-light optical microscope (POM), since in curved geometries, chirality is straightforwardly detectable, especially for high pitch values [12]. The textures observed in chromonics [13] are similar to the ones reported in several papers focused on chiral TLCs, even if LCLCs contain different ingredients that are thermodynamically balanced in the mesophases with respect to TLCs. Loss of water, temperature variations, changes in dopant solubility and the use of ions can affect the phase diagram and, consequently, the droplet state diagram [5].…”
Section: Introductionsupporting
confidence: 54%
See 2 more Smart Citations
“…29 Very recently, chirality has also been induced in DSCG confined in spherical geometries within a matrix (as shown by the emergence of Frank-Pryce textures). 30 With the aim to further broaden the scope of the use of DSCG as a chiral amplification agent, we decided to study in detail the relationship between the structure of the dopant, particularly its molecular charge and protonation state, and the degree of chiral amplification observed. The chosen systems were selected on the bases of hydrophilicity, availability in their enantiomerically pure forms and of low molecular weight.…”
Section: Introductionmentioning
confidence: 99%